Yeti, an essential Drosophila melanogaster gene, encodes a protein required for chromatin organization. - Messina, G.; Damia, E.; Fanti, L.; Atterrato, M.T.; Celauro, E.; Mariotti, F.R.; Accardo, M.C.; Walther, M.; Vernì, F.; Picchioni, D.; Moschetti, R.; Caizzi, R.; et al. (Journal of Cell Science, 2014)
The evolutionarily conserved family of Bucentaur (BCNT) proteins exhibits a widespread distribution in animal and plants, yet its biological role remains largely unknown. Using Drosophila melanogaster as a model organism, we investigated the in vivo role of the Drosophila BCNT member called YETI. We report that loss of YETI causes lethality before pupation and defects in higher-order chromatin organization, as evidenced by severe impairment in the association of histone H2A.V, nucleosomal histones and epigenetic marks with polytene chromosomes. We also find that YETI binds to polytene chromosomes through its conserved BCNT domain and interacts with the histone variant H2A.V, HP1a and Domino-A (DOM-A), the ATPase subunit of the DOM/Tip60 chromatin remodeling complex. Furthermore, we identify YETI as a downstream target of the Drosophila DOM-A. On the basis of these results, we propose that YETI interacts with H2A.V-exchanging machinery, as a chaperone or as a new subunit of the DOM/Tip60 remodeling complex, and acts to regulate the accumulation of H2A.V at chromatin sites. Overall, our findings suggest an unanticipated role of YETI protein in chromatin organization and provide, for the first time, mechanistic clues on how BCNT proteins control development in multicellular organisms.